The SHIELD (Safety & Health Improvement: Enhancing Law Enforcement Departments) Study: Feasibility and Findings - Kerry Stephen Kuehl; Diane L. Elliot; Linn eGoldberg; David P. MacKinnon; Bryan J. Vila; Jennifer L. Smith; Milica eMiocevic; Holly P. O'Rourke; Matthew eValente; Carol eDeFrancesco; Adrianna eSleigh; Wendy eMcGinnis (Frontiers Media S.A., 2014)
This randomized prospective trial aimed to assess the feasibility and efficacy of a team-based worksite health and safety intervention for law enforcement personnel. Four-hundred and eight subjects were enrolled and half were randomized to meet participants met for weekly, peer-led sessions delivered from a scripted team-based health and safety curriculum. Curriculum addressed: exercise, nutrition, stress, sleep, body weight, injury, and other unhealthy lifestyle behaviours such as smoking and heavy alcohol use. Health and safety questionnaires administered before and after the intervention found significant improvements for increased fruit and vegetable consumption, overall healthy eating, increased sleep quantity and sleep quality, and reduced personal stress.